Geometric effects on phase split at a large diameter T-junction - Wren, Elisabeth Mary Katie (2001)
The separation of gas-liquid flows is a necessary part of many industrial processes. Thus, it has received much attention over the years with the ultimate aim of reducing equipment costs whilst maintaining or improving efficiency. Traditionally, the Petroleum Industry has relied heavily on conventional vessel separators which are bulky, expensive and have a high inventory. Research has indicated that a cheap alternative may be a simple pipe junction. It has been shown that gas-liquid flows can be divided at pipe junctions in such a manner that there is a partial separation of the phases. The result is two streams - one richer in gas than the initial feed and the other richer in liquid. If the phases can be separated, albeit partially, at a simple pipe junction then the need for a large separator is diminished. Within this thesis the use of a simple T-junction is considered as a continuous, compact, economical partial phase separator with a minimal inventory for use within the oil industry. The main objective was to gain a better understanding of how a gas-liquid flow is divided at a large diameter T-junction and how the flow split is affected by T-junction geometry. Firstly, the orientation of the side arm from the horizontal was considered with both a regular (inlet arm diameter == branch arm diameter = 0.127m) T-junction and a reduced (branch arm to inlet diameter ratio = 0.6) T-junction. The side arm was placed horizontally (0'), vertically upwards (+90') and vertically downwards (-90') and the phase split of air water annular and stratified flows were investigated. To improve the phase separation characteristics of the regular T-junction, inserts protruding from the side arm into the main pipe were considered and for the junction with a vertically downwards side arm a U-bend was used to reduce the fraction of gas pulled through. The experimental investigation was expanded to incorporate the effect of placing two regular T-junctions in series. With the branch arm of the first placed vertically upwards (+90'). and the second vertically downwards (-90') a pure gas stream and a liquid rich stream were created from the multi-phase inlet. Reducing the sidearm diameter of the second junction lowered the fraction of gas drawn off in the liquid rich stream. The physical separation distance the T-junctions was found to have little effect on phase split. The interaction of the two junctions are interdependent and the phase split results from the two junction system was found to be more complex than simply considering the results of two individual T-junctions. Being able to predict the phase split at a junction is vital if they are to be considered seriously within industrial settings. The case of a regular T-junction with a vertically downwards (-90') side arm has received little specific attention. From the linear nature of the phase split results it was determined that if two key points could be accurately predicted then the phase split results can be determined. The "onset of gas take off', the fraction of liquid diverted down the branch arm when the first fraction of gas is pulled through, was successfully related to the bubble rise velocity of the gas entrained in the liquid column trapped in the branch arm. The "critical gas take off”, the fraction of gas diverted when all the liquid is drawn down the branch arm, was determined by relating the fluid flow to the motion of a failing particle.